(untitled) (American Journal of Education and Technology, 2024)
The purpose of this assessment is to identify gaps in access and availability of digital tools, as well as to evaluate their effectiveness in improving learning outcomes. A total of 300 students and 100 teachers were randomly selected from different government, private, and NGO higher secondary schools in GB. A questionnaire was created using the LIKERT scale and given to both teachers and students. Afterward, a statistical analysis was conducted. An effort was made to determine the variations in teachers’ gender using the T-test, and to analyze the differences in school types for students using one-way ANOVA. Revealing the average mean usage of digital educational tools by both teachers and students is (3.163272, 3.163272). The analysis indicates that both teachers and students have moderate usage level of digital educational tools. Additionally, both teachers and students lack advanced-level skills in using digital tools for teaching and learning, furthermore The usage level of educational digital tools in private schools is moderate, while in government schools it is low, and in NGO-based schools, it is again at a moderate level skills in learning. The usage level of digital educational tools in schools has significant implications for academic outcomes, teacher quality, and resource allocation. Integrating digital tools effectively can improve learning outcomes, increase accessibility, and personalize instruction.